(untitled) (World Bulletin of Management and Law, 2022)
Budgeting is actually a kind of financial planning. that the biggest social institution which is the government and the smallest which is the family do budget as one of their duties. Budgeting can be defined as planning expenses and incomes. Budget management is a management activity that managers use to design their activities in the future. By using this process, resources are allocated to each part of their sub-categories, which can be used to achieve the set goals. The purpose of this study is to investigate the effect of preparing an open budget on public financial management. The statistical population of the study includes the employees of the Iraqi Ministry of Finance. The sample size will be 356 people and considering the possibility of not returning a number of questionnaires or receiving distorted and unusable questionnaires, 370 questionnaires were sent. In the end, 356 questionnaires were received . In this research, a standard questionnaire with the opinion of experts was used to collect information. Data analysis was done using PLS and SPSS. For this purpose, three hypotheses were formed. The results of the data analysis showed that the preparation of an open budget leads to an increase in the level of transparency of the general financial management, the improvement of financial management control leads to the improvement of the accountability of the financial management. And among the applications of open budget, we can mention the reduction of corruption and the detection and prevention of budget wastage.